PHILOSOPHY AND MANAGEMENT: PARALLELISM AND CORRELATIONS IN THOUGHT EVOLUTIONS - Joseto N. Bernadas Jr; Eko Armada Riyanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to trace the historical parallelism and correlation in thought evolutions between Philosophy and Management. Historical parallelism speaks about the side-by-side progress of Philosophy and Management as distinct disciplines, whereas correlation deals with how they relate and interact with each other. Philosophy and Management, though in themselves are distinct and self-determining disciplines, are significantly interrelated. The central problem in this research paper is to find out when, how and why do Philosophy and Management mutually impact and enrich each other. Consequently, this study is conducted using the historical-hermeneutical research methodology, which requires reading a lot of resources on the thought evolutions of both sciences. The analysis progresses by first looking separately into the early thought developments of Philosophy and Management, wherein a general treatment on the nature and essential elements of both Philosophy and Management are laid down. Afterwards, the researcher focuses on how these two disciplines advanced and converged as related thoughts, which are articulated in the following formulations: “Philosophy in Management” and “Philosophy of Management.” Hopefully, the outcome of this study would significantly aid students to find more meaning and relevance in studying Philosophy and Management as correlated and integrated sciences. Keywords: Philosophy, Management, Parallelism, Correlations, Thought Evolutions